2013
DOI: 10.1021/ja3123653
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Pathway for the Epipolythiodioxopiperazine Acetylaranotin in Aspergillus terreus Revealed by Genome-Based Deletion Analysis

Abstract: Epipolythiodioxopiperazines (ETPs) are a class of fungal secondary metabolites derived from diketopiperazines. Acetylaranotin belongs to one structural subgroup of ETPs characterized by the presence of a seven-membered 4,5-dihydrooxepine ring. Defining the genes involved in acetylaranotin biosynthesis should provide a means to increase production of these compounds and facilitate the engineering of second-generation molecules. The filamentous fungus Aspergillus terreus produces acetylaranotin and related natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
128
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(130 citation statements)
references
References 41 publications
2
128
0
Order By: Relevance
“…18 In addition, all data for the ring parts in 6 were similar to those of known bisdethiobis(methylthio)-deacetylapoaranotin (10). 15 The cross-peaks from 8-H (δ 5.88) to C-11 (δ 171.5) and from 8′-H (δ 6.22) to C-11′ (δ 171.8) in HMBC data supported the same acyl side chains was attached at both C-8 and C-8′. Taken together, the structure of 6 was elucidated as shown in Figure 1.…”
Section: )mentioning
confidence: 73%
See 1 more Smart Citation
“…18 In addition, all data for the ring parts in 6 were similar to those of known bisdethiobis(methylthio)-deacetylapoaranotin (10). 15 The cross-peaks from 8-H (δ 5.88) to C-11 (δ 171.5) and from 8′-H (δ 6.22) to C-11′ (δ 171.8) in HMBC data supported the same acyl side chains was attached at both C-8 and C-8′. Taken together, the structure of 6 was elucidated as shown in Figure 1.…”
Section: )mentioning
confidence: 73%
“…We started to search for such inhibitors from natural sources using our established screening system, 12 leading to the discovery of tylopilusins 13 and citridone A and its derivatives. 14 Continuing our screening program, new compounds designated graphiumins A (1) to H (8), along with two structurally related known bisdethiobis(methylthio)-deacetylaranotin (9) 15 and bisdethiobis(methylthio)-deacetylapoaranotin (10), 15 were isolated from the culture broth of the marine-derived fungus Graphium sp. OPMF00224 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…HPLC-MS was carried out using a ThermoFinnigan LCQ Advantage ion-trap mass spectrometer with a reverse-phase C18 column (Alltech Prevail C18; 2.1 mm × 100 mm with a 3-μm particle size) at a flow rate of 125 μL/min. The solvent-gradient system for HPLC and the conditions for MS analysis were carried out as described previously (47).…”
Section: Methodsmentioning
confidence: 99%
“…iosynthesis, self-protection mechanisms, and functionality of gliotoxin and related epidithiodiketopiperazine (ETP) molecular species, such as chaetocin and acetylaranotin, are attracting ever-increasing attention as a consequence of findings from highthroughput genome sequencing projects, application of gene deletion technologies, and mass spectrometric analytical methodologies (1)(2)(3)(4)(5). Indeed, existing paradigms of gliotoxin ( Fig.…”
mentioning
confidence: 99%
“…Deletion of hlmI impaired holomycin biosynthesis and sensitized S. clavuligerus to exogenous holomycin, as had been observed for gliotoxin in A. fumigatus. Additionally, Guo et al revealed that in Aspergillus terreus, a fusion gene, ataTC, encodes both hydroxylation and disulfide bridge closure of biosynthetic intermediates during acetylaranotin formation (3). Wild-type A. terreus did not exhibit acetylaranotin sensitivity; however, no data were presented regarding the sensitivity of the ⌬ataTC strain to exogenous acetylaranotin.…”
mentioning
confidence: 99%